HOMESCHOOLING: FUNDAMENTAL RIGHTS, LIMITS AND LEGAL POSSIBILITIES: HOMESCHOOLING: FUNDAMENTAL RIGHTS, LIMITS AND LEGAL POSSIBILITIES (Revista Direito em Debate, 2021)
The present study aims to discuss the legal possibilities and the limits to legalize home education in Brazil. It brings a brief reflection on the regulatory moment of Brazilian education and distinguishes the concepts of education, teaching, learning, instruction and school. Then it conceptualizes Home Education as a possibility to learn without strictly following the school programs, through a more personalized course. It is a controversial subject. Despite the regulatory ban, there are countless families in Brazil who have opted for schooling at home. However, lawsuits have convicted parents who practice Homeschooling for "intellectual abandonment" litigation. Discusses the legal limits based on the dictates of Brazilian laws, in addition to  treaties and international conventions. It presents the possibility of the regulation and regulation of this modality of e
Keywords: Education. Homeschooling. Fundamental Rights. Legal Limits.